SENI SHARAF AL-ANÄ€M DAN RODAT DI PALEMBANG SEBAGAI SENI BERNUANSA KEAGAMAAN: THE ART OF SHARAF AL-ANÄ€M AND RODAT IN PALEMBANG AS RELIGIOUS ARTS - Zulkarnain Yani (Penamas, 2015)
This paper presents the results of research on the existence of Sharaf al-AnÄm and Rodat arts in the city of Palembang and surrounding areas in South Sumatera. Data collected through observations, interviews, and literature review. The results shows that along with the current development and many Islamic nuances arts in the city of Palembang, Sharaf al-AnÄm and Rodat art evidently still exist and present in the midst of the people of Palembang today. Tracing its history, the results of this study demonstrates that the art of Sharaf al-AnÄm and Rodat are used to commemorate 1st Muharram, the birth of Prophet Muhammad and of Isra 'and Mi'raj-ascension and night Journey, aqiqah the naming ceremony, the revelation of the Qur'an, and mutual forgiving event. Even, it is also used in the wedding process, both at the time of marriage licensing ritual and wedding procession. In addition, it is also used to welcome state guests. Keywords: Sharaf al-AnÄm, rodat, religious art, Palembang. Tulisan ini menyajikan hasil penelitian tentang keberadaan seni Sharaf alAnÄm dan Rodat di kota Palembang dan sekitarnya di Sumatera Selatan. Pengumpulan data dilakukan melalui observasi, wawancara, dan telah pustaka. Hasil penelitian menunjukkan, bahwa seiring dengan perkembangan zaman dan banyaknya seni-seni keagamaan yang bernuansa Islam di kota Palembang, seni Sharaf al-AnÄm dan Rodat ternyata masih tetap eksis dan hadir di tengah-tengah masyarakat kota Palembang hingga saat ini. Dengan menelusuri sejarahnya, hasil penelitian ini menunjukkan seni Sharaf al-AnÄm dan Rodat digunakan pada saat peringatan 1 Muharram, peringatan Maulid Nabi Muhammad SAW. dan peringatan Israâ€™ dan Miâ€™raj, aqiqah (marhabah), NuzÅ«l Al-Qurâ€™an dan Halal bi Halal. Bahkan, juga digunakan dalam proses pernikahan, baik pada saat akad nikah maupun arak-arak pengantin. Selain itu, juga digunakan untuk penyambutan para tamu negara.Kata Kunci: Sharf al-AnÄm, Rodat, seni keagamaan, Palembang.